A descriptive study of Swedish women with symptoms of breast inflammation during lactation and their perceptions of the quality of care given at a breastfeeding clinic - Kvist, Linda J (BioMed Central, 2007)
BACKGROUND: Women's perceptions of quality of care during episodes of breast inflammation have been scantily explored. It was the objective of the present study to describe a cohort of breastfeeding women with inflammatory symptoms of the breast during lactation regarding demographical variables, illness history and symptoms at first contact with a breastfeeding clinic and to explore their physical health status, psychological well-being and perceptions of quality of care received, at a six-week postal follow-up. METHODS: This is a descriptive study set at a midwife-led breastfeeding clinic in Sweden, which included a cohort of women with 210 episodes of breast inflammation. The women had taken part in a RCT of acupuncture and care interventions and were recruited between 2002 and 2004. Of the total cohort, 176 (84 %) responded to a postal questionnaire, six weeks after recovery. RESULTS: Of the 154 women for whom body temperature was recorded at the first visit, 80 (52%) had fever ranging from 38.1°C to 40.7°C. There was no significant difference between those with favourable outcomes (5 or less contact days) and those with less favourable outcomes (6 or more contact days) for having fever or no fever at first contact. Thirty-six percent of women had damaged nipples. Significantly more women with a less favourable outcome (6 or more contact days) had damaged nipples. Most women recovered well from the episode of breast inflammation and 96% considered their physical health and 97% their psychological well-being, to be good, six weeks after the episode. Those whose illness lasted 6 days or more showed less confidence in the midwives and in the care given to them. Twenty-one (12%) women contacted health care services because of recurring symptoms and eight of the 176 responders (4.5%) were prescribed antibiotics for these recurring symptoms. A further 46 women (26% of the responders) reported recurring symptoms that they managed without recourse to health care services. CONCLUSION: Initial fever may not be indicative of outcomes for women with inflammatory breast symptoms and treatment by antibiotic therapy may be necessary less often than has been supposed. Women who are also suffering from damaged nipples may need special attention. Those with protracted symptoms were less satisfied with care and showed less confidence in caregivers. International research collaboration might help us find the optimal level of antibiotic therapy for this group of women. This is an important consideration for the global community.